Construction of Underground Linkway using 3-Sided Pipe Roof Method at Keppel Station, Singapore - Ong, Terence; Tay, Joo King; Chen, Sai Sai (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Singapore is one of the most densely populated countries in the world. In this land-scarce city-state, public transport plays a crucial role in reducing road congestion, with the Mass Rapid Transit (MRT) system serving as a key component. The Circle Line (CCL) is one of the major lines within the MRT network, designed to connect key points across the island and improve overall transit efficiency. To complete the orbital loop of CCL, three new stations (Keppel, Cantonment and Prince Edward) between Harbour Front and Marina Bay stations are planned. However, the area around the three stations is heavily developed, posing significant challenges for underground construction. This paper presents the construction of a 52 m-long underground linkway at Keppel Station. This underground linkway was proposed to connect one of the entrances to the station’s main box. This underground linkway was constructed beneath a live 9-lane carriageway and above two operational MRT tunnels, all of which remained fully functional throughout the construction process. Due to the presence of the carriageway which could not be diverted, a trenchless construction method known as the pipe roof method was adopted instead of the conventional cut-and-cover technique. The method employed a three-sided pipe roof along with ground improvement at the base of the excavation rather than the typical full enclosure pipe box system. This paper outlines the key design considerations and construction challenges encountered. It also discusses the observed performance of the mined excavation and compares it with predictions from a two-dimensional finite element analysis (FEA). The successful application of this design methodology provides a valuable reference for similar underground linkway construction in dense urban environments.